2016
DOI: 10.1021/jacs.6b06247
|View full text |Cite
|
Sign up to set email alerts
|

Pd-Catalyzed Conversion of Alkynyl-λ3-iodanes to Alkenyl-λ3-iodanes via Stereoselective 1,2-Iodine(III) Shift/1,1-Hydrocarboxylation

Abstract: Alkynyl-λ(3)-iodanes have been established as alkynyl cation equivalents for the alkynylation of carbon- and heteroatom-based nucleophiles. Herein, we report an unprecedented reaction mode of this compound class, which features a Pd(II)-assisted 1,2-I(III) shift of an alkynylbenziodoxole. A Pd(II) catalyst mediates this shift and the subsequent interception of the transient vinylidene species with carboxylic acid (1,1-hydrocarboxylation). The product of this stereoselective rearrangement-addition reaction, β-o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
38
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 70 publications
(50 citation statements)
references
References 32 publications
2
38
1
Order By: Relevance
“…[13] Ochiai reported at ransition-metalfree anti-hydrochlorinationo fa lkynyl(phenyl)iodonium tetrafluoroborate by using LiCl/HOAc or HCl/MeOH, whereas the scope of the reaction was demonstrated for only ah andful of iodoniums alts. [14,15] By contrastt ot hese precedents,t he present anti-hydrochlorination, found during our study on the Pd-catalyzed 1,1-hydrocarboxylation, [6] was achieved under extremely simple conditions. Thus, the reaction between Ph-EBX 1a and pyridine hydrochloride (Py·HCl, 2equiv) proceeded smoothly in EtOAc at 50 8Cu nder air,a ffording the VBX product 2a in quantitative yield exclusively as a cis isomer (Table 1, entry 1).…”
contrasting
confidence: 73%
See 1 more Smart Citation
“…[13] Ochiai reported at ransition-metalfree anti-hydrochlorinationo fa lkynyl(phenyl)iodonium tetrafluoroborate by using LiCl/HOAc or HCl/MeOH, whereas the scope of the reaction was demonstrated for only ah andful of iodoniums alts. [14,15] By contrastt ot hese precedents,t he present anti-hydrochlorination, found during our study on the Pd-catalyzed 1,1-hydrocarboxylation, [6] was achieved under extremely simple conditions. Thus, the reaction between Ph-EBX 1a and pyridine hydrochloride (Py·HCl, 2equiv) proceeded smoothly in EtOAc at 50 8Cu nder air,a ffording the VBX product 2a in quantitative yield exclusively as a cis isomer (Table 1, entry 1).…”
contrasting
confidence: 73%
“…We disclosed palladium-catalyzed 1,1-hydrocarboxylation of various substituted EBXs by a1 ,2-iodine(III) shift, affordingV BXs bearing an enol carboxylate moiety (Scheme 1a). [6,7] Miyake reported anti-addition of phenols to aryl-EBXs under visible-light irradiation (Scheme 1b), in which the primary VBX product readily transforms into iodovinylether. [8] More recently,W aser has found simple conditions that allow fort he anti-addition of sulfonamides and phenolst oa lkyl-EBXs with retention of the BX moiety in the products.…”
mentioning
confidence: 99%
“…81 The reactions, which were promoted by the [Pd(OAc)(2-methylallyl)]2/1,5-cyclooctadiene system under very mild conditions (r.t.), led to the selective formation of the alkenylbenziodoxoles 17. Density functional theory (DFT) calculations indicated that this unprecedented rearrangement/addition process involves the formation of a Pd-vinylidene intermediate VI, via 1,2-shift of the iodine(III) fragment on the initially formed π-alkyne species V. Then, a formal 1,1-hydroxycarboxylation takes place by nucleophilic addition of the carboxylate anion on the α-carbon of the vinylidene intermediate VI, and subsequent protodemetalation of the resulting alkenyl-palladate VII.…”
Section: Methodsmentioning
confidence: 99%
“…Recently, Hirao et al have reported a Pd(II) catalyzed 1,1‐hydrocarboxylation of alkynyl benziodoxole 1 as shown in Scheme (a) . The palladium pre‐catalyst and the ligand combination play a crucial role in the reaction.…”
Section: Alkynylationmentioning
confidence: 99%